Boumediene vs. Verdugo-Urquidez: The Battle for Control over Extraterritoriality at the Southwestern Border - Netta Rotstein (Washington University Law Review, 2016)
This Note aims to track the Hernandez reasoning, situate it within the historical development of the extraterritoriality doctrine, and evaluate its scope and implications. Part I provides a detailed overview of the development of the extraterritoriality doctrine of the US Constitution. It also describes the modern precedent governing this area of law. Part II critically examines the Hernandez decision in light of its theoretical approach to extending constitutional protections abroad. Part III evaluates the implications and limitations of Hernandez and proposes a more accurate interpretation of the extraterritoriality doctrine as a guide for resolving this and future incidents of violence by CBP agents. Ultimately, this Note argues that the court’s narrow interpretation of constitutional language and inadequate application of extraterritorial principles when deciding whether to deny or extend rights to foreign nationals injured abroad at the hands of government actors is dangerous. Such interpretation encourages inconsistencies and perpetuates a system of lawless law enforcement at the border, where CBP agents have plenary power to act with little oversight and accountability by US magistrates. Instead, this Note proposes an alternative framework for analyzing future extraterritorial incidents of violence at the United States-Mexico border.
Keywords: Boumediene; Verdugo-Urquidez; US border; constitutional law; Hernandez; extraterritoriality